(untitled) (Journal of Informatics Education and Research, 2025)
This research study introduces a model that uses surveys to analyse the spread of false information, with a specific focus on the influence of social and cultural factors as well as historical connections. The study uncovers a notable change in the consumption of digital news, highlighting the need for companies and news providers to modify their media strategy in order to effectively connect with an audience that heavily relies on social media. Evidence suggests that there is a prevailing doubt about the credibility of social media content, emphasising the urgent importance of fact-checking and verifying information. The study also examines the interpersonal interactions within groups on the evaluation of information, observing diverse reactions and the influence of social approval on the articulation of conflicting perspectives. Moreover, the study highlights the impact of cultural and historical significance on the level of involvement on social media and the swift dissemination of cultural and historical falsehoods. The research concludes by emphasising the significance of educational resources and heightened awareness in countering the dissemination of false information and improving public comprehension.